Policing and race in America : economic, political, and social dynamics - Ward, James D. (James Dale), 1959- (Lexington Books, 2018)
This collection explores policing and race in relationship to political challenges, economic realities, and social ramifications. This is done through the use of evidence-based research and established best practices as presented in fourteen chapters written by accomplished scholars across various academic disciplines.